Implementasi Program Kampus Mengajar dalam Pembelajaran Bahasa Indonesia - Lasmiatun, Lasmiatun; Ramadhaniati, Ratih Utami; Darningwati, Darningwati (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to describe the implementation ofthe campus teaching programin learning Indonesian in class VI SD N 53 OKU.The type of research used is descriptive. The method used is a descriptive method with data collection techniques in the form of interviews, tests and documentation. The research results showed that before the program, students had unbalanced reading habits, with 47.37% of students reading frequently and 52.63% of students rarely reading. However, after the GELINAS and ABM programs, students showed significant changes, with 100% of students arguing that they often read and campus teaching could improve students' reading abilities. In fact, two student swho have participated in the ABM program have achieved optimal results, with scores of 84 and 64 out of 100, indicating that the program is effective in improving students'reading abilities. From the results of these data it can be concluded that the GELINAS and ABM programs have a significant impact in improving students' reading habits. With this program, students can improve their reading skills and achieve optimal results.